Protective mechanism of polysaccharides from Phellinus linteus on H9c2 cardiomyocyte injury induced by hypoxia/reoxygenation - Xiaoyu Ren; Qingxian Mei; Yuan Zhou; Lili Jiang; Fei Liu; Jinfeng Wang (BMC Research Notes)
Abstract Objective This study aimed to explore the protective mechanism of Phellinus linteus polysaccharides (Phps) against hypoxia/reoxygenation (H/R)-induced injury in H9c2 cardiomyocytes, focusing on oxidative stress, apoptosis, and PI3K-AKT pathway regulation. Results H9c2 cardiomyocytes were divided into control, H/R model, and Phps-treated groups (low/medium/high doses). The H/R model (established by exposing cells to hypoxia for 10 h followed by 4 h of reoxygenation.) induced significant injury: cell viability decreased, SOD activity reduced by 45%, and Bcl-2 expression declined at both mRNA and protein levels, while LDH activity increased by 66%, MDA content surged by 99%, and Bax expression (mRNA/protein) and p-PI3K and p-AKT levels were upregulated, with statistical significance (P < 0.05 vs. control). Compared to the H/R model group, the Phps treatment (low, medium, high) groups showed a significant increase in H9c2 cardiomyocytes viability, SOD activity, and mRNA and protein expression levels of Bcl-2. The LDH activity, MDA content, mRNA levels of Bax, and protein expression levels of Bax, p-PI3K and p-AKT significantly decreased, with statistical significance (P < 0.05). These results suggest that Phps may improve H/R induced damage in H9c2 cardiomyocytes by downregulating the ratio of Bax/Bcl-2 through the PI3K-AKT pathway.